The perspective of corporate governance reformation from the lens of institutional theory - Abdullah, Zaimah; Chizema, Amon; Chandren, Sitraselvi (2018)
The purpose of this conceptual paper is to address the importance of examining the link between corporate governance and foreign equity investment through the right theoretical lens. The paper focuses on the discussion of corporate governance reformation in Malaysia that gradually converged towards Anglo-American model at the pinnacle of Asian financial crisis 1997/1998. By embracing institutional theory, the actions taken by majority of organizations in Malaysia in the aftermath of the crisis are justified and the reactions of foreign investors towards the corporate governance recuperation in Malaysia’s institutional corporate setting are explained. This paper also provides in depth explanation of the applied theory, which under the scope of neo-institutional theory that accentuated on legitimacy. Besides, this paper claims the relevant use of this theory with the subject discussed, thus argues the significant importance of theoretical aspects of the institutional context to the study of governance change and institutional dynamic setting in emerging country like Malaysia. In summary, the use of apt lens of theory to justify the reactions and actions taken by the actors is imperative as an essence to convey a period of momentous changes in the storyline of the governance change from the perspective of the foreign investors.